What does it take to get elected in a post-communist democracy? Explaining the success and failure of parliamentary candidates in Estonia - Trumm, Siim (SAGE, 2016)
The literature on post-communist democracies has traditionally suggested that organisational strength is considerably less important for electoral success than extensive media-based campaigns. Recent studies on party-level electoral dynamics, however, indicate that this might not be the case any longer. Building on these insights, this study goes beyond the party-level analyses of electoral success and failure by focusing on the electoral fortunes of individual candidates in a post-communist democracy. Using original data from the 2011 Estonian Candidate Survey, this paper looks at the comparative impact of candidates’ campaign spending and the strength of their local party organisation, alongside other potentially relevant characteristics, on their likelihood of getting elected and vote share. The findings suggest that candidates’ electoral performance in Estonia is still first and foremost shaped by their own campaign spending. In addition, I find evidence that candidates fare better if they have prior local-level and national-level political experience, conduct more personalised campaigns, and are positioned higher up on their party’s district-level list.